Implementation of The Bantul Traditional’s Market Policy as Empowerment of UMKM Pasca COVID-19 Pandemic - Daffa Aqshal Maulana; Muhammad Eko Atmojo (PERSPEKTIF, 2023)
The purpose of this article is to find out how to implement the Bantul Traditional's Market policy as empowerment of UMKM post COVID-19 pandemic. This was done considering the current situation of the transition to post-pandemic COVID-19 which previously had quite a significant impact on the UMKM sector and traditional's markets in Bantul Regency. Therefore, with this policy it is hoped that the government can provide public services to overcome problems that occurred before and prepare for future situations. This study uses qualitative methods using data triangulation. Based on the results of the study, it was concluded that the implementation of the current policy was in accordance with the indicators of the theory of policy implementation used. It is evident from the program planning and implementation, all of which aim to empower UMKM in the Bantul Traditional's Market. However, there are also obstacles that still occur and have the potential to hinder the smooth implementation of policies, namely the government's response which tends to be slow when problems occur and must wait according to the applicable SOPs. The government is urged to be more responsive in overcoming problems so that the problems that occur do not pile up and cause big problems